The use of mycophenolate mofetil area under the curve. Issue 3 (May 2021) - Chakrabarti, Katherine; Frame, David; Al Abbas, Mousa; McCune, W. Joseph
Abstract : Purpose of review: Although mycophenolate mofetil (MMF) has been used successfully to treat a myriad of autoimmune diseases, its complex pharmacokinetics make it difficult to determine the true drug exposure for an individual patient. This review summarizes the body of literature focused on the gold standard measurement of the area under the curve (AUC) of mycophenolic acid (MPA), the active metabolite of MMF. Recent findings: Fixed dosing of MMF leads to highly variable drug exposure. Retrospective series have reported improved clinical outcomes when a minimum AUC value from 0 to 12 h (AUC0–12h ) ≥30 mg h/l is achieved. MPA levels are affected by various drug interactions, hypoalbuminemia, and renal insufficiency and the measurement of free rather than total MPA levels is prudent in some situations. A limited number of studies employing prospective dose adjustment of MMF based on AUC0–12h measurements have yielded mixed results. Summary: Given the wide range of MPA AUC encountered in autoimmune diseases, dose adjustments of MMF based on AUC rather than fixed dosing of MMF should be considered in both clinical practice and clinical trials. Limited sampling strategies have been proposed to improve clinical feasibility of measurements, but a standard is yet to be defined.